Mucormycosis at a tertiary care centre in Gujarat, India. Issue 6 (9th March 2017) - Patel, Atul K.; Patel, Ketan K.; Patel, Kamlesh; Gohel, Swati; Chakrabarti, Arunaloke
Summary: The prevalence of mucormycosis is reportedly high in India, although the studies are mainly from north and south India only. We analysed the mucormycosis cases at tertiary care centres of West India. We retrieved the clinical details of all the patients with probable and proven mucormycosis diagnosed at Sterling Hospital and ID clinic at Ahmedabad, Gujarat over the period from 1 January 2013 through 30 April 2015. The data were analysed to determine demography, risk factors, underlying diseases, site of infection and outcome of these patients. A total of 27 patients with the median age of 50 (16‐65) years were diagnosed with mucormycosis during the period. Rhino‐orbital‐cerebral mucormycosis was the most common (51.9%) presentation. Majority (55.6%) of the patients had uncontrolled diabetes with or without ketoacidosis; 25.9% patients had no underlying disease and most of them (85.7%) had cutaneous mucormycosis. In this group, the mortality was 25.9% and an equal percentage of patients were lost to follow up; 14 (51.9%) patients could complete 6 weeks of amphotericin B therapy. All patients who completed antifungal therapy survived except one. Like other parts of India, uncontrolled diabetes was the predominant risk factor for mucormycosis in our group. Patients completing 6 weeks of amphotericin B treatment were likely to survive.